2009
DOI: 10.1007/s10549-009-0450-x
|View full text |Cite
|
Sign up to set email alerts
|

The proteins FABP7 and OATP2 are associated with the basal phenotype and patient outcome in human breast cancer

Abstract: MethodsWe analysed 48,000 gene transcripts in 132 invasive breast carcinomas to identify two novel genes (OATP2 and FABP7) significantly associated with BP (defined by cytokeratin (CK)5/6 and/or CK14 positivity). Using a series of invasive breast carcinoma cases (n=899), prepared as tissue microarrays, we assessed OATP2 and FABP7 protein expression using immuncocytochemistry to investigate associations with clinicopathological variables, patients" outcome and ability to refine BP classification. ResultsA total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
40
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 49 publications
9
40
2
Order By: Relevance
“…have demonstrated significant correlations between FABP7 immunoreactivity and absence of ER/PR expression in breast cancer. 23,51 One group suggested that elevated levels of FABP7 may underlie high histological grade and poor prognosis in basal-like breast tumors, 51 but the other group observed a better prognosis in FABP7-positive basal-like breast tumors. 23 These data highlight the need for further studies to clarify the various roles of FABPs and their ligands in breast cancer formation and progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…have demonstrated significant correlations between FABP7 immunoreactivity and absence of ER/PR expression in breast cancer. 23,51 One group suggested that elevated levels of FABP7 may underlie high histological grade and poor prognosis in basal-like breast tumors, 51 but the other group observed a better prognosis in FABP7-positive basal-like breast tumors. 23 These data highlight the need for further studies to clarify the various roles of FABPs and their ligands in breast cancer formation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 In particular, FABP7 and FABP4 have been shown to be associated with the basal phenotype/patient outcome in breast cancer and as a novel prognostic factor in obese breast cancer patients, respectively. 22,23 Using a mouse mammary tumor model, alternative activation of different nuclear receptors (RAR and PPAR␤) by RA was shown to be mediated by different intracellular lipid-binding proteins (CRABP2 in the case of RAR and FABP5 in the case of PPAR␤). 11,12 This RA dichotomy may help to explain the opposing effects of RA on different subsets of breast cancer.…”
mentioning
confidence: 99%
“…This approach stratified the transcripts on their ability to classify samples based on the occurrence of DM (n = 35) compared with those without DM (n = 93), as previously described [15,16]. These five proteins are encoded by genes/transcripts' data analysed by artificial neuronal network.…”
Section: Patients and Tumoursmentioning
confidence: 99%
“…This is a well-characterised series of primary operable invasive breast carcinomas patients less than 71 years of age, treated in a single institution, which has been previously investigated for a wide range of prognostic factors [31][32][33][34]. Data on a range of patient, pathology and biomarkers were available.…”
Section: Study Populationmentioning
confidence: 99%